Activity-Independent Effects of CREB on Neuronal Survival and Differentiation during Mouse Cerebral Cortex Development. (20th December 2016) - Landeira, Bruna Soares; Santana, Themis Taynah da Silva; Araújo, Jéssica Alves de Medeiros; Tabet, Elie I; Tannous, Bakhos A; Schroeder, Timm; Costa, Marcos R
Abstract: Neuronal survival and morphological maturation depends on the action of the transcription factor calcium responsive element binding protein (CREB), which regulates expression of several target genes in an activity-dependent manner. However, it remains largely unknown whether CREB-mediated transcription could play a role at early stages of neuronal differentiation, prior to the establishment of functional synaptic contacts. Here, we show that CREB is phosphorylated at very early stages of neuronal differentiation in vivo and in vitro, even in the absence of depolarizing agents. Using genetic tools, we also show that inhibition of CREB-signaling affects neuronal growth and survival in vitro without affecting cell proliferation and neurogenesis. Expression of A-CREB or M-CREB, 2 dominant-negative inhibitors of CREB, decreases cell survival and the complexity of neuronal arborization. Similar changes are observed in neurons treated with protein kinase A (PKA) and Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) inhibitors, which also show decreased levels of pCREBSer133. Notably, expression of CREB-FY, a Tyr134Phe CREB mutant with a lower Km for phosphorylation, partly rescues the effects of PKA and CaMKII inhibition. Our data indicate that CREB-mediated signaling play important roles at early stages of cortical neuron differentiation, prior to the establishment of fully functional synaptic contacts.